2018
DOI: 10.4293/jsls.2017.00064
|View full text |Cite
|
Sign up to set email alerts
|

Trifecta Outcomes to Assess Learning Curve of Robotic Partial Nephrectomy

Abstract: Background and Objectives:The learning curve for achieving desirable perioperative outcomes in robot-assisted partial nephrectomy (RAPN) has not been well studied. Information is available regarding “trifecta” outcomes of no complications, no positive margins, warm ischemia time (WIT) of ≤25 minutes, and a ≤15% decrease in postoperative glomerular filtration rate (GFR). This study was conducted to assess the impact of the learning curve on surgical outcomes in patients undergoing RAPN.Methods:We reviewed 131 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…RAPN has emerged as an alternative to LPN for removal of renal tumors for shortening the learning curve associated with laparoscopy. The benefits are a greater range of motion, greater manual dexterity and flexibility, optically magnified imaging, enhanced visualization, precision of control and tremor reduction resulting resulting in reduced total operation time and less amount of experience required by the surgeon [43][44][45][46]. In their study Omidele et al showed that RAPN is a safe, effective treatment modality for small renal masses, the outcomes are better than LPN and is a technically easier procedure to master.…”
Section: Robot-assisted Partial Nephrectomy(rapn)mentioning
confidence: 99%
See 3 more Smart Citations
“…RAPN has emerged as an alternative to LPN for removal of renal tumors for shortening the learning curve associated with laparoscopy. The benefits are a greater range of motion, greater manual dexterity and flexibility, optically magnified imaging, enhanced visualization, precision of control and tremor reduction resulting resulting in reduced total operation time and less amount of experience required by the surgeon [43][44][45][46]. In their study Omidele et al showed that RAPN is a safe, effective treatment modality for small renal masses, the outcomes are better than LPN and is a technically easier procedure to master.…”
Section: Robot-assisted Partial Nephrectomy(rapn)mentioning
confidence: 99%
“…In their study Omidele et al showed that RAPN is a safe, effective treatment modality for small renal masses, the outcomes are better than LPN and is a technically easier procedure to master. This goal can be reached after >61-90 cases at a rate of 20 cases per year [43]. ''Trifecta" is a statement used in radical prostatectomy and now Hung et al [47,48] introduced the outcomes of partial nephrectomy as; providing negative surgical margins, minimal renal function decrease, and absence of complications in the same patient.…”
Section: Robot-assisted Partial Nephrectomy(rapn)mentioning
confidence: 99%
See 2 more Smart Citations
“…The increased number of RAPNs performed by a surgeon correlates with a lower WIT and hence improvement in the patient outcome. Studies have shown the learning curve to achieve an ideal WIT of <25 min ranges from 44 to 60 cases [38] , [39] .…”
Section: Surgical Factorsmentioning
confidence: 99%